Biofouling control by phosphorus limitation strongly depends on the assimilable organic carbon concentration. (15th September 2020) - Javier, Luisa; Farhat, Nadia M.; Desmond, Peter; Linares, Rodrigo Valladares; Bucs, Szilárd; Kruithof, Joop C.; Vrouwenvelder, Johannes S.
Abstract: Nutrient limitation is a biofouling control strategy in reverse osmosis (RO) membrane systems. In seawater, the assimilable organic carbon content available for bacterial growth ranges from about 50 to 400 μg C·L −1, while the phosphorus concentration ranges from 3 to 11 μg P·L −1 . Several studies monitored biofouling development, limiting either carbon or phosphorus. The effect of carbon to phosphorus ratio and the restriction of both nutrients on membrane system performance have not yet been investigated. This study examines the impact of reduced phosphorus concentration (from 25 μg P·L −1 and 3 μg P·L −1, to a low concentration of ≤0.3 μg P·L −1 ), combined with two different carbon concentrations (250 C L −1 and 30 μg C·L −1 ), on biofilm development in an RO system. Feed channel pressure drop was measured to determine the effect of the developed biofilm on system performance. The morphology of the accumulated biomass for both carbon concentrations was characterized by optical coherence tomography (OCT) and the biomass amount and composition was quantified by measuring total organic carbon (TOC), adenosine triphosphate (ATP), total cell counts (TCC), and extracellular polymeric substances (EPS) concentration for the developed biofilms under phosphorus restricted (P-restricted) and dosed (P-dosed) conditions. For both carbon concentrations, P-restricted conditions (≤0.3 μg P·L −1 ) limited bacterial growth (lower values of ATP, TCC). A faster pressure drop increase was observed for P-restricted conditions compared to P-dosed conditions when 250 μg C·L −1 was dosed. This faster pressure drop increase can be explained by a higher area covered by biofilm in the flow channel and a higher amount of produced EPS. Conversely, a slower pressure drop increase was observed for P-restricted conditions compared to P-dosed conditions when 30 μg C·L −1 was dosed. Results of this study demonstrate that P-limitation delayed biofilm formation effectively when combined with low assimilable organic carbon concentration and thereby, lengthening the overall membrane system performance. Graphical abstract: Image 1 Highlights: At a high C content, P restriction caused a faster pressure drop increase with time. At a low C content, P restriction caused a slower pressure drop increase with time. Phosphorus limitation restricted microbial growth but changed biofilm structure. P-restricted biofilms were more porous and covered a larger area in the channel. Biofilm spatial distribution had strong implications on membrane performance.